2023
DOI: 10.1111/jfpe.14328
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of sonication and equilibrium‐modified atmosphere packaging to improve storage stability of “Angelino” plums during extended storage

Abstract: This work focuses on the combined effects of ultrasound treatment (100, 200, and 300 W for 5 min) and equilibrium-modified atmosphere packaging (EMAP) to enhance the storage stability based on pH, aw, gas compositions in headspace, color changes (L*, a*, b*), organic acids, and texture profile of fresh "Angelino" plums for 120 days at 4 C. The results were expressed that pH values were increased (3.19-initial to 3.69/300 W-3.86/control) and Brix values were decreased (16.9-initial to 14.70/control-15.3/100 W) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The results indicated the high level of CO 2 (40%) in combination with the normal level of O 2 (20%) maintained better chemical properties compared with control samples. In addition, complementary approach with MAP such as 1-MCP (Hu et al, 2020), ultraviolet light (Souza et al, 2022), and ultrasound (Caner et al, 2023) revealed that the complementary methods affected the maintaining of the physiological quality, delayed senescence process, and reduced ethylene production. Thus, complementary treatments can increase the shelf life of agricultural and horticultural products.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated the high level of CO 2 (40%) in combination with the normal level of O 2 (20%) maintained better chemical properties compared with control samples. In addition, complementary approach with MAP such as 1-MCP (Hu et al, 2020), ultraviolet light (Souza et al, 2022), and ultrasound (Caner et al, 2023) revealed that the complementary methods affected the maintaining of the physiological quality, delayed senescence process, and reduced ethylene production. Thus, complementary treatments can increase the shelf life of agricultural and horticultural products.…”
Section: Introductionmentioning
confidence: 99%